"They Are Our Brothers and Sisters": Why Zapatismo Matters to Independent Labour in Mexico - Khasnabish, Alex (Anthropologica, 2022)
In this paper I seek to illuminate the bases upon which the Mexican independent labour movement and the indigenous Zapatista movement have been able to engage in a politics of accompaniment, a politics based on mutual respect and support without sacrificing autonomy or difference. I examine how this intersection emerged, the grounds that make it possible, and the significance of such an intersection for the Zapatistas and independent labour. This analysis is also an attempt to explore political relationships and possibilities that transgress traditionally understood boundaries and to begin to imagine new relationships and ways of envisioning and practicing politics.